DETERMINATION OF METASTATIC CAPACITY IN PRIMARY LUNG CANCER CELLS: REFLECTION OF PATIENT PROFILE IN THE CLINIC USING IN VITRO METHODS - Seçil Yılmaz; Medine Doğan Sarıkaya; Elif Yaşar; Burcu Şen Bağcı; Özlem Canöz; Ömer Önal (Sabiad)
Objective: There is a scarcity of in vivo models that accurately reflect tumor growth and metastasis in cancer research. Research using cell lines with increasing passage numbers may give misleading results because the tumor loses its characteristic feature. Primary culture is the best method to represent the cellular profile of cancer patients in the laboratory environment. Therefore, we worked with patient-derived primary culture. The most common subtype of the most diagnosed lung cancer worldwide is Non-Small Cell Lung Cancer (NSCLC). Therefore, we aimed to determine patient-specific metastatic capacities by comparatively examining the migration abilities of primary cancer cells of NSCLC patients on the same platform.Materials and methods: The migration abilities of primary cancer cells of NSCLC patients were demonstrated through wound healing assays on cisplatin and non-cisplatin groups, and measurements were made with Image J software.Results: In the results of the wound healing assays performed on the cancer cells of five patients, it was observed that there was correlation between the wound widths, wound areas, wound closure percentages, and metastasis in the groups with and without cisplatin in Patient 3, Patient 4, and Patient 5.Conclusion: To reflect the profile of patients visiting the clinic using patient-derived primary tumor cells, the wound healing assay can be used as a tool to demonstrate tumor behaviors, such as the patients’ responses to treatment and their metastasis-forming capacity. Detailed studies are needed in a larger population so that the physician can use in vitro tools in the decision support mechanism.